The promise of reconciliation - C. Perrin; S. Veitch (Law Text Culture, 1998)
Bringing them home, The Report of the National Inquiry into the Separation of Aboriginal and Torres Strait Islander Children from their Families concludes that "The Australian practice of Indigenous child removal involved both systematic racial discrimination and genocide as defined by international law" (266). This conclusion raises a number of questions that the Report takes up and contextualises with reference to a developing jurisprudence focused upon the nation's relationship to its human rights violations. In particular, for the Report, this relationship is central to current Australian debates about, and concerns with, the history of its treatment of Indigenous peoples. Knowing and remembering the violence of the nation's past, acknowledging, commemorating and so coming to terms with it, is, for the Report, a precondition of national reconciliation.